Prognostic significance of 2019 Asian Working Group for Sarcopenia update on definition of sarcopenia. (25th November 2020) - Saito, K; Matsue, Y; Kamiya, K; Saito, H; Ogasahara, Y; Kitai, T; Konishi, M; Maekawa, E; Iwata, K; Jujo, K; Wada, H; Kasai, T; et al.
Abstract: Background/Introduction: Sarcopenia plays a major role in the pathophysiology of frailty and is associated with worse outcome in the elderly population including patients with heart failure. A recent update of the most common definition of sarcopenia in Asia, Asian Working Group for Sarcopenia (AWGS2019), included significant changes in the diagnostic algorithm with newly dividing sarcopenia into severe and "non-severe" sarcopenia. Purpose: The objective of this study was to evaluate the differences between AWGS2014 and AWGS2019 in patients with heart failure. Methods: In the multicenter prospective FRAGILE-HF registry, which included elderly (≥65 years old) patients who were hospitalized with heart failure, we studied 865 patients (80±8 years old, 42% female). All-cause death in 1-year follow-up was tracked. Results: Based on the original version of AWGS (AWGS2014), 183 patients (21%) were diagnosed with sarcopenia, which was associated with higher age, lower physical performance, less muscle mass, and greater heart failure risk (all p<0.001) as well as higher rate of all-cause death (HR 1.90, p=0.004 after adjustment by multivariable regression). Those patients with sarcopenia by AWGS2014 were reclassified mainly to severe sarcopenia (155, 84.7%) by AWGS2019, and 25 (13.7%) and 2 (1.1%) were classified into sarcopenia and non-sarcopenia. Meanwhile, 24 (3.5%) and 4 (0.6%) of patients without sarcopenia by AWGS2014 were reclassified into sarcopenia and severe sarcopenia, respectively. Although severe sarcopenia by AWGS2019 was associated with higher age, lower physical performance, less muscle mass, and greater heart failure risk (all p<0.001), patients with "non-severe" sarcopenia was rather younger (p<0.001) and had better physical performance (p=0.021) despite less muscle mass (p<0.001) than those without sarcopenia. Multivariate Cox analysis demonstrated severe sarcopenia by AWGS2019 was an independent prognostic factor (HR 1.77, p=0.014), but "non-severe" sarcopenia was not (HR 1.52, p=0.37). The prognosis of patients who were reclassified from non-sarcopenia to sarcopenia or severe sarcopenia were comparable to those remained non-sarcopenia. When added to other risk factors, the prognostic predictability of AWGS2019 was significantly lower than AWGS2014 (net reclassification improvement −0.26, p=0.025). Conclusions: About a half of "non-severe" sarcopenia in AWGS2019 were patients without sarcopenia in AWGS2014. The prognosis of such patients who were newly diagnosed as sarcopenia was good, resulting in low overall prognostic predictability of AWGS2019. A further consideration for diagnostic algorithms of sarcopenia may be warranted in patients with heart failure. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): Japan Heart Foundation